Advanced technical textiles and materials in defence: is the EU up to the challenge? - Marsili, M.; Borges, J. (International Forum on Advanced and digitalised Smart Textiles (IFAST), 2021)
This paper aims to reflect on the challenges of adopting new technologies in Technical Textiles and Materials for defence concerning the current readiness and capacities in the European Union. Identified bottlenecks are the manufacturing readiness, the supply chain capacity and autonomy, and the knowledge and technical skills required.